2003
DOI: 10.1289/ehp.6226
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-dependent distribution of persistent organochlorine pollutants in urban foxes.

Abstract: The colonization of urban and suburban habitats by red foxes (Vulpes vulpes) provides a novel sentinel species to monitor the spread of anthropogenic pollutants in densely populated human settlements. Here, red foxes were collected in the municipal territory of Zürich, Switzerland, and their perirenal adipose tissue was examined for persistent organochlorine residues. This pilot study revealed an unexpected pattern of contamination by polychlorinated biphenyls (PCBs), with significantly higher levels of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 43 publications
1
12
1
Order By: Relevance
“…The lower levels of DP in female fish could be attributed to the transfer of DP from mothers to their eggs. Clear sexual differences in PCBs and other organochlorine pesticides have been previously observed in frogs (Rana ornativentris and Rana japonica) and red foxes (Vulpes vulpes), resulting from the maternal transfer of these chemicals in females (Kadokami et al, 2004;Dip et al, 2003).…”
Section: Residue Levelsmentioning
confidence: 87%
“…The lower levels of DP in female fish could be attributed to the transfer of DP from mothers to their eggs. Clear sexual differences in PCBs and other organochlorine pesticides have been previously observed in frogs (Rana ornativentris and Rana japonica) and red foxes (Vulpes vulpes), resulting from the maternal transfer of these chemicals in females (Kadokami et al, 2004;Dip et al, 2003).…”
Section: Residue Levelsmentioning
confidence: 87%
“…Peirce and Van Daele (2006) have shown that eating garbage may provide earlier maturation, higher growth rates, and gain some calorific benefit. However, foraging close to human settlements may be risky, because many of the carnivorous species are regarded as pests, and are persecuted because of the possibility of being poisoned (Birks 1998;Dip et al 2003). There is also a possible risk of damage to or blockage of the digestive track (Sadove & Morreale 1990).…”
Section: Discussionmentioning
confidence: 99%
“…They postulated that these high lead concentrations could have adverse effects on predators such as small falconiformes due to bioaccumulation. Dip et al (2003) found high concentrations of organochlorine pollutants in urban red foxes (Vulpes vulpes). However, they documented that this resulted in high levels of mortality among adult males but not females.…”
Section: Disease and Pollutionmentioning
confidence: 98%